Effectiveness of Mediterranean Diet on Prevention and Management of Prediabetes and Type 2 Diabetes (Bangladesh Journal of Medical Science, 2025)
In recent years, growing evidence linking nutrition to chronic degenerative diseases has prompted researchers to identify optimal dietary patterns for health maintenance. Among various diets, the Mediterranean Diet (MD) has emerged as the most extensively studied and promising approach. This review synthesizes current literature on the MD’s effectiveness for type 2 diabetes (T2DM) and prediabetes, drawing from PubMed, Scopus, ProQuest, Google Scholar, Cochrane, and Embase databases (2011-2024) using keywords including ‘Mediterranean Diet,’ ‘MD,’ ‘Type 2 Diabetes,’ and ‘Prediabetes.’ The MD emphasizes plant-based foods, particularly minimally processed whole grains and olive oil, with studies showing higher olive oil consumption correlates with reduced diabetes incidence. Research demonstrates significant improvements in glycaemic control, including reduced fasting plasma glucose and HbA1c levels, with high MD adherence associated with an 18% lower T2DM risk compared to low adherence. While limitations exist in dietary adherence across populations, the MD remains a practical, evidence-based strategy for diabetes prevention and management, with compelling epidemiological evidence supporting its role in metabolic health improvement for both T2DM and prediabetes.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 385-394